Detection of Epstein-Barr virus encoded small RNA genes in oral squamous cell carcinoma and non-cancerous oral cavity samples - Arghavan Zebardast; Yousef Yahyapour; Maryam Seyed Majidi; Mohammad Chehrazi; Farzin Sadeghi (BMC, 2021)
Abstract Background Epstein-Barr Virus (EBV) is a human oncogenic virus that can lead to cancer in lymphoid and epithelial cells and is one of the hypothesized causes of oral cavity lesions including oral squamous cell carcinoma (OSCC), but the etiological association remains undetermined. The present investigation aimed to explore the EBV presence, viral load, and EBV-encoded small RNA (EBER) sequence variation in tissue samples of patients with OSCC and other oral cavity lesions including oral lichen planus (OLP), and oral irritation fibroma (OIF). Methods In total, 88 oral cavity samples (23 with OSCC, 29 with OLP, and 36 with OIF diagnosis) were examined by Real-Time PCR technique and some of them were sequenced. Results Viral EBER sequence was detected in 6 out of the 23 OSCC (31.4%), 6 out of the 29 OLP (20.7%), and 3 out of the 36 OIF cases (8.3%). The mean EBV copy number was higher in OSCC samples (1.2 × 10−2 ± 1.3 × 10−2 copies/cell) compared to OLP (2.2 × 10−3 ± 2.6 × 10−3 copies/cell) and OIF (2.4 × 10−4 ± 2.0 × 10−4 copies/cell) samples, although this difference was not statistically significant (P = 0.318). The EBER gene was amplified and sequenced in 5 OSCC, 3 OLP, and 2 OIF samples with high EBV viral load. One OSCC, two OLP, and two OIF isolates showed different nucleotide variations compared with EBV-WT and AG876 prototype sequences: C6834T, C6870T, C6981T, C7085T, C7085G, and C7094T. Conclusion In our study the presence of more than one genome copies per tumor cell indicates the possible role of EBV infection in oral cancers. However, more studies should be conducted to clarify the role of EBV in OSCC carcinogenesis.